Proceedings the international symposium on Austronesian diaspora : Austronesian diaspora a new perspective July 18-23, 2016 in Bali, Indonesia / editor, Bagyo Prasetyo, Titi Surti Nastiti, Truman Simanjuntak - THE INTERNASIONAL SYMPOSIUM ON AUSTRONESIAN DIASPORA 2016: Bali; Bagyo Prasetyo; Titi Surti Nastiti; Simanjuntak, Truman (Gadjah Mada University Press, 2016)
ix, 594 hlm. : ilus. ; 26 cm.